Atividade antileishmania do extrato hidroetanólico e frações de Cinnamomum Verum J.S. Presl (Lauracea) - JESUS, Caroline Martins de (2023)
Leishmaniasis represents a serious public health problem affecting millions of people annually. Currently, the therapeutic options for its treatment have important adverse effects, being essential the search for new active substances. Cinnamomum verum, popularly known as cinnamon, has been widely studied for its pharmacological activities, including its antileishmania potential, however, most studies are associated with its essential oil and, in addition, there is no information about the possible mechanism. of action exercised by this species. Therefore, in this study we evaluated the antileishmanial activity of the hydroethanolic extract and fractions of the leaves of C. verum and sought to identify the mechanism of action associated with cell death. Cytotoxic activity on promastigotes and amastigotes forms of Leishmania amazonensis and on RAW 264.7 macrophages was performed using the MTT colorimetric assay, and from the biomonitored fractionation in promastigotes forms, the most active fraction was selected for chemical characterization through Gas Chromatography coupled to Mass Spectrometry, and the investigation of the type of cell death associated with the biological effect is also carried out using the Ethidium Bromide and Acridine Blue assay over a period of 4 hours. Bearing in mind that this is a plant species with important pharmacological potential, but with few studies focused on extracting the leaves with solvents of different polarities tested in Leishmania, this research brings important information about its chemical composition and possible mechanisms of action. It is important to emphasize that the execution of the techniques exposed here benefited from partnerships with laboratories from other institutions, as well as the use of equipment with advanced technology, guaranteeing the reliability and quality of the results obtained, in addition to the use of accessible protocols with possible data replication. The Hexanic fraction, rich in phytol, proved to be highly selective for in vitro promastigotes and amastigotes forms of L. amazonensis, having apoptosis as cell death mechanism. These data reinforce the leishmanicidal potential of the hexanic fraction of C. verum and its possible use as a pharmacological adjuvant in the treatment of leishmaniasis, a disease that still affects a significant number of people around the world, and can also be used in the production of the most varied formulations for therapeutic purposes, thus generating both a social and economic impact with the reduction of expenses destined for its treatment.